Eeffects of the Pilates Method on water on functional capacity and body balance of elderly people - Schlemmer, Gessica Bordin Viera (2020)
: Study with the objective of investigating the effects of the Pilates Method on water in terms of submaximal functional capacity and dynamic balance of 18 elderly women. The training was carried out for eight weeks and the six-minute walk test (6MWT) and Timed Up and Go Test (TUG) were used. The training improved the distance covered in the 6MWT and reduced the time of the TUG, promoting a better functional capacity and dynamic balance of elderly women.Keywords: Balance Postural; Exercise Tolerance; Aging.